Remand in Spain and the state's liability: two reforms that remain outstanding - Simón Castellano, Pere (Revista Catalana de Dret Públic, 2021)
This article examines the controversial measure of remand in Spain in the light of two striking facts: firstly, the ubiquity of this preventative measure in judicial practice (at the beginning of the year, 16% of the prison population were pretrial detainees) and, secondly, a compensation system based on state liability that, in the case of acquittal, has proven ineffective since 1985 and that has recently been shaken to its core by judgements of the European Court of Human Rights and the declaration by Spain's own Constitutional Court of the unconstitutionality of a number of provisions of Article 294 of the country's Organic Law on Judicial Powers. In addition to reviewing the developments leading up to the current situation, the article sets out the parameters for the debate on how to properly tackle two legislative reforms that now appear more pressing than ever.
La presó provisional i la responsabilitat patrimonial de l’Estat jutge: dues reformes pendents
Aquesta recerca examina la polèmica institució de la presó provisional a Espanya a l’albir de dues realitats punyents: d’una banda, l’omnipresència d’aquesta mesura cautelar com a pràctica judicial —a principis d’any, un 16% de la població reclusa es trobava en situació de presó preventiva—; de l’altra, un sistema d’indemnització, en cas d’absolució, per responsabilitat patrimonial de l’Estat jutge, que s’ha mostrat ineficaç des de 1985 i que recentment s’ha vist sacsejat en els seus fonaments per la intervenció del Tribunal Europeu de Drets Humans i la declaració, per part del Tribunal Constitucional, de la inconstitucionalitat de diferents incisos de l’article 294 de la LOPJ. L’article planteja, més enllà del repàs del procés que ens ha portat fins a la situació actual, els termes del debat per poder afrontar amb garanties dues reformes legislatives, que s’intueixen més necessàries que mai.
Keywords: wrongful remand; remand; right to compensation; state liability; presumption of innocence; Emerging; Scopus